Pelatihan Penulisan Aksara Ulu Sumatera Selatan Bagi Komunitas Pusat Studi Sejarah dan Budaya Silampari - Yadri Irwansyah (Jurnal Nusantara Berbakti, 2024)
The Ulu script is a form of native South Sumatran cultural heritage that lives among the Uluan (inland) people of South Sumatra. As a form of original regional writing tradition, it is important to preserve the Ulu script among the younger generation so that this cultural heritage is not lost. However, due to the lack of knowledge and understanding of the younger generation, the Ulu script seems to be foreign. Therefore, this training is important apart from aiming to provide understanding and also to preserve cultural heritage. The method in this training is through introduction, understanding letters, punctuation and direct training practice. As a result of this training, participants can understand the basic letters of the Ulu script and practice writing directly either through conventional media or through digitalized MS Word.